Definition of a standard lymphadenectomy in surgery for pancreatic ductal adenocarcinoma: a consensus statement by the International Study Group on Pancreatic Surgery (ISGPS) - Tol, Johanna A. M. G.; Gouma, Dirk J.; Bassi, Claudio; Dervenis, Christos; Montorsi, Marco; Adham, Mustapha; Andrén-Sandberg, Ake; Asbun, Horacio J.; Bockhorn, Maximilian; Büchler, Markus W.; Conlon, Kevin C.; Fernández-Cruz, Laureano; et al. (Surgery, 2014)
Background - The lymph node (Ln) status of patients with resectable pancreatic ductal adenocarcinoma is an important predictor of survival. The survival benefit of extended lymphadenectomy during pancreatectomy is, however, disputed, and there is no true definition of the optimal extent of the lymphadenectomy. The aim of this study was to formulate a definition for standard lymphadenectomy during pancreatectomy. - Methods - During a consensus meeting of the International Study Group on Pancreatic Surgery, pancreatic surgeons formulated a consensus statement based on available literature and their experience. - Results - The nomenclature of the Japanese Pancreas Society was accepted by all participants. Extended lymphadenectomy during pancreatoduodenectomy with resection of Ln's along the left side of the superior mesenteric artery (SMA) and around the celiac trunk, splenic artery, or left gastric artery showed no survival benefit compared with a standard lymphadenectomy. No level I evidence was available on prognostic impact of positive para-aortic Ln's. Consensus was reached on selectively removing suspected Ln's outside the resection area for frozen section. No consensus was reached on continuing or terminating resection in cases where these nodes were positive. - Conclusion - Extended lymphadenectomy cannot be recommended. Standard lymphadenectomy for pancreatoduodenectomy should strive to resect Ln stations no. 5, 6, 8a, 12b1, 12b2, 12c, 13a, 13b, 14a, 14b, 17a, and 17b. For cancers of the body and tail of the pancreas, removal of stations 10, 11, and 18 is standard. Furthermore, lymphadenectomy is important for adequate nodal staging. Both pancreatic resection in relatively fit patients or nonresectional palliative treatment were accepted as acceptable treatment in cases of positive Ln's outside the resection plane. This consensus statement could serve as a guide for surgeons and researchers in future directives and new clinical studies.